1997
DOI: 10.2981/wlb.1997.022
|View full text |Cite
|
Sign up to set email alerts
|

Survival of black grouseTetrao tetrixin the French Alps

Abstract: S u rv iv a l ra te s a re n e c e s s a ry f o r c a lc u la tin g a llo w a b le h a rv e sts a n d fo r m o d e llin g p o p u la tio n p e rfo rm a n c e . S u rv iv a l ra te s f o r 9 3 b la c k g ro u s e Tetrao tetrix e q u ip p e d w ith ra d io ta g s in tw o p o p u la tio n s o f th e s o u th e rn F re n c h A lp s w e re e s tim a te d . A n n u a l su rv iv a l ra te s o f h e n s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 27 publications
(33 reference statements)
6
54
1
Order By: Relevance
“…Previous research has demonstrated acute reproductive costs on survival of various species (Williams 1966, Erikstad et al 1998, including some grouse species (Tetraoninae, Angelstam 1984, Caizergues and Ellison 1997, Hagen et al 2007, Blomberg et al 2013. We extend the reproductive costs to a chronic effect on subsequent reproduction that, to our knowledge, has not been shown for grouse, but has been shown for other taxa (e.g., Røskaft 1985, Gustafsson andSutherland 1988).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous research has demonstrated acute reproductive costs on survival of various species (Williams 1966, Erikstad et al 1998, including some grouse species (Tetraoninae, Angelstam 1984, Caizergues and Ellison 1997, Hagen et al 2007, Blomberg et al 2013. We extend the reproductive costs to a chronic effect on subsequent reproduction that, to our knowledge, has not been shown for grouse, but has been shown for other taxa (e.g., Røskaft 1985, Gustafsson andSutherland 1988).…”
Section: Discussionmentioning
confidence: 89%
“…Reproductive costs to survival exist in both female (Blomberg et al 2013) and male sagegrouse (Boyko et al 2004), and have also been documented in black grouse (Tetrao tetrix;Angelstam 1984, Caizergues andEllison 1997), lesser prairie-chickens (Tympanuchus pallidicinctus; Hagen et al 2005Hagen et al , 2007, and willow ptarmigan (Lagopus lagopus; Hannon et al 2003). Further, physiological reproductive costs have been detected in male black grouse (Angelstam 1984, Kervinen et al 2012) and sage-grouse (Vehrencamp et al 1989).…”
Section: Introductionmentioning
confidence: 95%
“…Black Grouse populations may be significantly affected by predation (Angelstam 1984;Caizergues and Ellison 1997) -even though most of the Black Grouse's predators prey upon eggs and chicks (Summers et al 2004), there were several species of predator in the study area that could be capable of taking adults, including Eagle Owl Bubo bubo, Goshawk Accipiter gentilis, Golden Eagle Aquila chrysaetos, Pine Marten Martes martes and Red Fox Vulpes vulpes. Furthermore, remains of several adults killed by unidentified birds of prey were found during our study period.…”
Section: Correlates Of Roost Locationmentioning
confidence: 99%
“…However, given that the Black Grouse may use igloos even in relatively mild weather, when it may not be necessary for energetic reasons, an anti-predator function has also been suggested (Bergerud and Gratson 1988;Marjakangas 1990). This hypothesis seems rational because predation mortality, mainly due to large birds of prey, is particularly high (Angelstam 1984;Caizergues and Ellison 1997). Furthermore, an increased vulnerability to predation during years with little snow has been detected (Spidsø et al 1997).…”
Section: Introductionmentioning
confidence: 98%
“…The decline in grouse breeding success are commonly associated with increased rates of nest predation, especially by mammalian predators (Marcström et al 1988, Baines 1991, Caizergues & Ellison 1997, Kurki et al 1997, 1998, Kauhala & Helle 2002. In Fennoscandia, two hypotheses are generally put forward to explain the observed increases in predation pressures.…”
Section: Introductionmentioning
confidence: 99%